2015
DOI: 10.1016/j.procir.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Cutting Fibrous Composite Materials: Current Practice

Abstract: Using fibre reinforced polymers (FRP) is increasing across many industries. Although FRP are laid-up in the near-net shape, several cutting operations are necessary to meet quality and dimensional requirements. Modelling of cutting is essential to understand the physics of the cutting phenomena and to predict quality and cost of products. This paper aims at reviewing the current practice in modelling of cutting FRP including analytical, numerical, mechanistic and empirical approaches, with emphasis on analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Modelling of machining can be analytical, numerical or empirical. The current practice of modelling of composites machining was reviewed in [5]. Extensive research was conducted on numerical modelling of machining composites.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling of machining can be analytical, numerical or empirical. The current practice of modelling of composites machining was reviewed in [5]. Extensive research was conducted on numerical modelling of machining composites.…”
Section: Introductionmentioning
confidence: 99%
“…Significant work was done to investigate the drilling of CFRP materials, including reviews completed by Panchagnula et al [ 9 ] and Lissek et al [ 10 ], outlining the significance of process monitoring to ensure hole quality. Kahwash et al highlighted the current practice of modelling the cutting process of CFRPs and the use of 2D orthogonal cutting due to its simplicity and computational advantage [ 11 ]. Liu et al from experimental results on drilling of composite laminates concluded that the variation between materials’ elastic modulus affected the drilled hole diameters [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of composite materials is increasing in several industries such as automotive, aerospace and sports equipment. This may attribute to their superior properties to metallic materials such as the high strength-to-weight ratio, good impact resistance, sound mechanical properties and they are also cheaper as compared to metal products [1,2]. Polymer matrix composites (PMCs) reinforced with ceramic nanoparticles are the most widely used composites due to their low cost and ease of fabrication [3,4].However, the machining of these materials is very difficult to achieve due to the existence of the hard-ceramic phases that accelerate the wear rate of cutting tools [5].…”
Section: Introductionmentioning
confidence: 99%